2013
DOI: 10.1152/ajpheart.00250.2013
|View full text |Cite
|
Sign up to set email alerts
|

The loss of sustained Ca2+signaling underlies suppressed endothelial nitric oxide production in preeclamptic pregnancies: implications for new therapy

Abstract: ]i) and NO in umbilical vein endothelium of normal and PE subjects that is still intact and on the vessel luminal surface. This was achieved by dissection and preloading with fura 2 and DAF-2 imaging dyes, respectively, before subsequent challenge with ATP (100 M, 30 min). As a control to reveal the content of active endothelial nitric oxide synthase (eNOS) per vessel segment, results were compared with a maximal stimulus with ionomycin (5 M, 30 min). We show for the first time that normal umbilical vein endot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 28 publications
3
30
0
Order By: Relevance
“…And while EDHF plays an important role in augmenting increased uterine blood flow, if not causing it in certain situations, it also seems likely changes in [Ca 2+ ] i signaling may be equally important to NO, PGI2 and EDHF function given the action of 2-APB in each case. Consistent with this, it is also relevant that we reported recently that the endothelial cells of umbilical cords from PE women at late term show defects in sustained and coordinated endothelial Ca 2+ bursting (Krupp et al 2013) and while NO output was measured and a decrease observed, we did not measure PGI2 or EDHF.…”
Section: Physiologic and Anatomic Adaptation Of Vasculature To Presupporting
confidence: 91%
See 1 more Smart Citation
“…And while EDHF plays an important role in augmenting increased uterine blood flow, if not causing it in certain situations, it also seems likely changes in [Ca 2+ ] i signaling may be equally important to NO, PGI2 and EDHF function given the action of 2-APB in each case. Consistent with this, it is also relevant that we reported recently that the endothelial cells of umbilical cords from PE women at late term show defects in sustained and coordinated endothelial Ca 2+ bursting (Krupp et al 2013) and while NO output was measured and a decrease observed, we did not measure PGI2 or EDHF.…”
Section: Physiologic and Anatomic Adaptation Of Vasculature To Presupporting
confidence: 91%
“…By late gestation (3 rd trimester) the vessel architecture of the uterus is essentially developed and any further increases in blood flow are now dependent on a sustained vasodilation of those existing vessels. Clinically, it is the mid to late gestation period when most cases of PE present themselves to physicians, and PE subjects are known to show reduced capacity for vasodilation (Kenny et al 2002; Krupp et al 2013; Yamamoto et al 2010). …”
Section: Physiologic and Anatomic Adaptation Of Vasculature To Prementioning
confidence: 99%
“…Such information suggests future endothelial-targeted therapies that protect and even improve endothelial CCE mechanisms mediated via IP3R/TRPC interaction could not only improve vasodilatory responses to G-protein coupled activators of PLC-beta but also growth factor activation of PLC-gamma. This type of global rescue of responses may be critical in applications aimed at disease states such as preeclampsia where sustained Ca2+ responses to ATP (and other agonists) have otherwise failed and associated vasodilation is lacking (Krupp, et al 2013). …”
Section: Resultsmentioning
confidence: 99%
“…18,19 Further, agoniststimulated NO production is reduced in isolated umbilical arteries from women with preeclampsia. 20 Phosphorylation of endothelial NO synthase and changes in intracellular Ca 2+ concentrations in endothelial cells are the main determinants of NO production.…”
Section: Endothelium-derived Vasodilatorsmentioning
confidence: 99%
“…29 The reduction in PGI 2 production may be because of impaired endothelial Ca 2+ signaling as determined in intact umbilical vein endothelium from patients with preeclampsia. 19 Reactive oxygen species may also contribute to inhibition of PGI 2 production. …”
Section: Prostacyclinmentioning
confidence: 99%